INDONESIAN EFL TEACHERS' SELF-EFFICACY AND THEIR SUCCESSFUL TEACHING PERFORMANCE - Rizka Indahyanti (Elite : English and Literature Journal, 2016)
The purpose of this research aimed to investigate the influence of Teachers' Self-efficacy on their teaching performance in the classroom setting. The role of teachers' years of teaching experience in their self-efficacy was also investigated. The method applied waa a qualitative descriptive research with interview as the instrument. The participants of this research were two Indonesian EFL teachers. The years of teaching experience were 2 years for novice teacher and 21 years for experienced teacher. The result of this research showed that experienced teacher has higher sense of self-efficacy than novice teacher. It also showed that years of teaching experience influence to teachers' self-efficacy.